Economies and favours: What's in a word? - Nicolette Makovicky; David Henig (economic sociology. perspectives and conversations, 2022)
People do things with words. Metaphors, jokes, utterances, idioms and vernaculars are basic elements of how people communicate, create their communities and organisations, and act on and make sense of the world they inhabit (Austin 1962; Lakoff and Johnson 1980). Consider, for example, these ways of talking about drinking and eating: in Kenya, someone might ask you to buy them a cup of tea; in Morocco they might ask for a coffee; and in Lebanon you might be surprised to be asked to bring sweets when dealing with an official. In Turkey, you might be asked for 'cash for soup', a dish traditionally eaten at the end of a night of heavy drinking.
Keywords: 300